Analisis Teori Looking-Glass-Self Cooley: Fenomena Eksistensi Akun Kampus Cantik dan Konstruksinya di Masyarakat - Shafira, Maya; Komariah, Siti; Wulandari, Puspita (The Indonesian Journal of Social Studies, 2022)
The virtual universe always has its role in getting a massive response from society. This research elaborates on the presence of the @/kampus.cantik account on Instagram media and its relation to self-concept and its construction in society based on the theory of Symbolic Interaction according to Charles Horton Cooley’s view. The research method in this paper uses a qualitative approach with literature study methods referring to various related literature. This study uses data collection techniques in the form of analyzing and collecting various literature review materials through books, journals, articles, news websites and other credible sources. The results of the study show that there is relevance between Cooley’s symbolic interaction theory regarding the Looking Glass Self and self-concept resulting from the appearance of the @/kampus.cantik account accompanied by the circulation of beauty standards created by society and other external factors. In connection with this social construction, it sharpens beauty standards in society and normalizes the objectification of women.